Design and Development of a Web-Based New Student Admission Information System at SMP Negeri 1 Raya - Fathiya Hasyifah Sibarani; Triase Triase; Rahmad Syuhada; Vicky Setia Gunawan (STMIK Methodist Binjai, 2026)
SMP Negeri 1 Raya is one of the schools that needs an information system to help its academic process. One of the academic processes carried out every year is the admission of new students. Currently, the registration system for new student candidates is carried out by visiting the school and bringing the files that have been previously informed. The problems that occur in the admission process are the accumulation of files so that it takes a long time when looking for certain files, losing files, and it takes a long time to manage new student admission data. This makes the new student admission process inefficient. Based on the problems, this study aims to build a student registration information system that help schools and facilitate parents in the registration process of prospective students. This research uses Waterfall as a system development method with sequential stages. The results of the study show that the information system built is in accordance with the needs and facilitates the registration process of prospective students for schools and parents.